Cell polarity, cell adhesion, and spermatogenesis: role of cytoskeletons - Li, Linxi (F1000Res, 2017)
In the rat testis, studies have shown that cell polarity, in particular spermatid polarity, to support spermatogenesis is conferred by the coordinated efforts of the Par-, Crumbs-, and Scribble-based polarity complexes in the seminiferous epithelium. Furthermore, planar cell polarity (PCP) is conferred by PCP proteins such as Van Gogh-like 2 (Vangl2) in the testis. On the other hand, cell junctions at the Sertoli cell–spermatid (steps 8–19) interface are exclusively supported by adhesion protein complexes (for example, α6β1-integrin-laminin-α3,β3,γ3 and nectin-3-afadin) at the actin-rich apical ectoplasmic specialization (ES) since the apical ES is the only anchoring device in step 8–19 spermatids. For cell junctions at the Sertoli cell–cell interface, they are supported by adhesion complexes at the actin-based basal ES (for example, N-cadherin-β-catenin and nectin-2-afadin), tight junction (occludin-ZO-1 and claudin 11-ZO-1), and gap junction (connexin 43-plakophilin-2) and also intermediate filament-based desmosome (for example, desmoglein-2-desmocollin-2). In short, the testis-specific actin-rich anchoring device known as ES is crucial to support spermatid and Sertoli cell adhesion. Accumulating evidence has shown that the Par-, Crumbs-, and Scribble-based polarity complexes and the PCP Vangl2 are working in concert with actin- or microtubule-based cytoskeletons (or both) and these polarity (or PCP) protein complexes exert their effects through changes in the organization of the cytoskeletal elements across the seminiferous epithelium of adult rat testes. As such, there is an intimate relationship between cell polarity, cell adhesion, and cytoskeletal function in the testis. Herein, we critically evaluate these recent findings based on studies on different animal models. We also suggest some crucial future studies to be performed.